(untitled) (International Journal of Sustainable Energy and Environmental Research, 2014)
In this study, we illustrate the results which were obtained using a comparative protocol concerning hazelnut production framework with special references to Turkey and Italy. Investigation includes supply, exports and several internal organization patterns. Emphasis was laid on proposing agro-forest biomass derived by hazelnut cultivations for renewable energy production via small-scale applications, in order to enhance farmers’ income within Turkish individual agro-districts. Due to importance of Turkey in world hazelnut trade, it is interesting to project some enhancements which have been already carried out in Italy. A consolidated protocol using DEA analyses gave evidence to the possibility of stabilizing both domestic and world prices along with differentiating hazelnut farmer’s income.